Introduction to the symposium on Ingrid Robeyns’s Limitarianism - Drydyk, Jay (Journal of global ethics, 2025)
In her book Limitarianism, Ingrid Robeyns draws attention to a specific type of moral response to inequality that is often ignored by social and political philosophers, even though it is widely experienced by the public. This is: condemnation of excess. The human capability for justice is based in part on a sense of fairness as proportionality, and the excessive wealth that we may witness both in history and in the contemporary world beggar any reasonable sense of proportionality. Meanwhile, Robeyns shows that excessive wealth also outrages other components of our sense of justice: our care and compassion for the well-being of others; our respect for freedom and aversion to domination; and our revulsion at ill-gotten gains. Three key questions raised by the contributors to this symposium might be highlighted: Where should we draw the ‘riches line’ that marks off excessive wealth? Can Western limitarianism harmonize with Asian philosophies such as Confucianism, which focus on social harmony in which there is enough for all? Why does Robeyns advocate for a cap on wealth as an ideal but not as a point in her practical program for action?